Propuesta metodológica de un modelo de Benchmarking para centros de investigación y desarrollo tecnológico (I+D) del sector petrolero (2010)
Excellence models formulatded by some countries through their national awards for quality management are considered an instrument promoting business competitiveness, and they are primarily based on the comprehensive management strategy, processes and culture. This last element seeks to ensure organizations a continuous learning process which is leveraged in a large proportion by the Benchmarking. Accordingly, Benchmarking is now considered a key element of integrated business management because its structured, systematic and continuous development and promotion of organizational learning and continuous improvement of organizations facing a constantly and fast changing environment.Based on the foregoing, the international oil sector organizations have highlighted the need for a Benchmarking model for R & D management to enable them to effectively determine what are the critical factors of success to ensure, identify, adapt and implement, and the best practices to ensure desired levels of performance for this management.This article proposes a methodology Benchmarking model for the R & D management, which arises from the compilation and analysis of information and experiences on the subject by some of the world class identified and selected R & D centers in the oil sector; in addition, this article aims to guide the R & D centers in this sector who wish to implement a simple and logical process of Benchmarking to manage their R & D, through the implementation of some basic steps and tools for this.